2012
DOI: 10.1002/clc.21975
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias in Women

Abstract: There are important gender differences in cardiac electrophysiology that affect the epidemiology, presentation, and prognosis of various arrhythmias. Women have been noted to have higher resting heart rates compared to men. They also have a longer QT interval, which puts them at an increased risk for drug-induced torsades de pointes. Women with atrial fibrillation are at a higher risk of stroke, and they are less likely to receive anticoagulation and ablation procedures compared to men. Women have a lower risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 43 publications
2
13
1
Order By: Relevance
“…Various studies have demonstrated marked differences between males and females in ischaemic heart disease, in terms of risk factors, aetiology, disease manifestation, diagnostic modalities, the use and effectiveness of various therapies, and prognoses . Likewise, several studies have revealed sex differences in heart failure and cardiac arrhythmias . This has led to worldwide research and educational initiatives on the specific characteristics of cardiovascular disease in women …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have demonstrated marked differences between males and females in ischaemic heart disease, in terms of risk factors, aetiology, disease manifestation, diagnostic modalities, the use and effectiveness of various therapies, and prognoses . Likewise, several studies have revealed sex differences in heart failure and cardiac arrhythmias . This has led to worldwide research and educational initiatives on the specific characteristics of cardiovascular disease in women …”
Section: Introductionmentioning
confidence: 99%
“…2 -4 Likewise, several studies have revealed sex differences in heart failure 5 and cardiac arrhythmias. 6 This has led to worldwide research and educational initiatives on the specific characteristics of cardiovascular disease in women. 7 -9 In 2008, the Working Group of the European Society of Cardiology published a position statement on the classification of cardiomyopathies.…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences may affect diagnostic and therapeutic interventions in a wide variety of medical conditions including cardiac arrhythmias [32]. In our study, when atrial conduction times were compared before and after RF ablation according to sexes; no signi cant difference was observed between the two groups in male patients, while there were signi cant differences in all parameters except for intra-atrial conduction delay in female patients.…”
Section: Discussionmentioning
confidence: 52%
“…At the present stage of studies, in the prevention of SCD in females, criteria are applied which are currently the same for males, although the benefits in the group of females have not been sufficiently documented [27]. The precondition for undertaking a decision concerning ICD implantation is that the patients qualified for the procedure had the chance to live for at least one year in good general state [2].…”
Section: Sudden Cardiac Deathmentioning
confidence: 99%